MESIN PENGERING KAYU SEDERHANA UNTUK HOME INDUSTRI - Murni Murni (Diponegoro University, 2007)
Dryer machine of wood is made to fulfill need of wood in order to produce raw of drying wood is notdepended weather. Making of dryer of wood usually requiree investment cost more expensive . it is heavyfor home industry .Inovation of simple dryer machine is done with flowing steam naturally and base onanalyzing it shows that drying can achieve moistur content 12 persen